Women Empowerment and the Role of Gender Equality toward Development in Nigeria - Uwais, Idrees Abdullahi; Maidala, Aliyu Ahmad; Adamu, Sanusi (Darul Yasin Al Sys, 2025)
The aim of this paper is to uncover the role of Women Empowerment and the Role of Gender Equality toward development in Nigeria. To achieve this purpose, qualitative methodology is employed and secondary sources of data were used as instruments of data collection. Based on the data analyzed, findings of the study show that the use of a women's labor force in the economic development of the country is minimal and the role of women across different dimensions is less reflected in the country. The political economic and social sphere of the country is large, reserved for men and few women. The place of women in society is also relegated to contributing minimally to the social development of the country. In addition to that, women's rights are not properly being protected in order for women to participate in various issues of their country but are subjected to violations. Moreover, women are highly affected by societal problems and less emphasis is given to their participation in protecting the environment. In a nutshell, women are empowered and gender equality is achieved so that women can play their role in economic, social, political, and environmental areas and the country cannot achieve development with the recognition of one gender to participation in all areas. The fact that women constitute one quarter the entire population of the country makes empowering them to be an active part of all development, initiatives in the country a compelling the challenges. Therefore, this paper calls for the strong commitment of the government to empower women and utilize all the potentials of the country to bring about development.